Pemanfaatan Mol Limbah Sayuran sebagai Pupuk Organik Cair pada Tanaman Padi (Oryza sativa L.) - Nana Ariska; Yusrizal Yusrizal; Jasmi Jasmi (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2019)
This service aims to provide information so that farmers can utilize and apply liquid organic fertilizer from vegetable waste (MOL) to rice plants in the village of Cot Darat, Sama Tiga District, West Aceh Regency. The method used to achieve these objectives is through counseling using participatory and on-site practice. The stages of its implementation are through counseling methods in the form of material exposure on vegetable waste MOL, discussion of farmer groups on site, training in processing organic waste into biocomposers together with farmer groups. The results of this service show that the level of knowledge and understanding of technology for processing vegetable waste into organic fertilizer can be absorbed (controlled) by rice farmers. All members of the group consist of various ages ranging from 30 to 50 years. One indicator in determining work productivity in conducting business development is the age level, where the age of farmers who are relatively young is stronger, work smart, easy to accept new innovations.